ChemInform Abstract: Organocopper‐Triggered Cyclization of Conjugated Diene‐ynes: Diastereo‐ and Enantioselective Synthesis of Indenes. Issue 13 (March 2016) - Arif, Tanzeel; Borie, Cyril; Tintaru, Aura; Naubron, Jean‐Valere; Vanthuyne, Nicolas; Bertrand, Michele P.; Nechab, Malek
Abstract: A new method for the construction of chiral indenes bearing two stereogenic centers is developed.